Bibliometric Analysis of Ethical Behavior in Education Using VOSviewer - Rais Hidayat; Yuyun Elizabeth Patras; Herlina Usman; Yusuf Gunawan; Tustiyana Windiyani (Journal of Innovation in Educational and Cultural Research, 2023)
The research theme of ethical behavior, particularly in educational organizations, is of great importance. There have been many publications on ethical behavior, but there has been no research to identify and summarize publications on it comprehensively. This research aims to clarify the history and predict the hotspots of ethical behavior themes in the future. This research method uses bibliographical analysis using the VOSviewer application. Data was sourced from the Scopus database between 1982 and 2021, downloaded into Excel 2016, and processed by VOSviewer. Bibliometric maps are formed by VOSviewer software automatically.Results of the research, which began with a search on the article title through the keyword "ethic* behav*," obtained 957 documents. After being limited by publication between 1983 and 2021, 590 papers were accepted. Then it was restricted again based on articles, reviews, and English obtained from as many as 399 documents. The United States, United Kingdom, and Canada are the most productive countries writing this theme. Department of Management, Haworth College of Business, Western Michigan University, United States; School of Management, the University of Alaska Fairbanks, Fairbanks, United States; andDepartment of Basic Psychology and Methodology, University of Murcia, Murcia, Spain; they are the most prolific Institutions with this theme. The Journal of Business Ethics, Ethics and Behavior, and Science and Engineering Ethics are the journals that expose ethical behavior the most. Meanwhile, the most prolific authors are Deshpande S.P, Joseph J, Cronan T.P, Leonard N.K., Al Habusi H., and Gino F. Conclusion of the research with the theme of ethical behavior is generally associated with behavior in business, the prerequisite occurrence of ethical behavior in organizations, and variables that can improve and shape ethical behavior. In line with the development of societal progress, ethical behavior research requires more intensive attention, especially in education organizations, because the quality and sustainability of human life, business, and education lie in the quality of ethical behavior.